Effectiveness Assessment Portfolio in Science Subject Based on Google Form for Students Tanjung Harapan Elementary School - Triutama, Yosua William; Lukman, Lukman; Hasdin, Hasdin (PT. Riset Press International, 2025)
One of the implementations of the right technology in education is the development of digital assessment, such as utilizing Google Forms to support the learning process. Assessment is an integral part of learning and functioning as a tool For measuring and assessing students' understanding and development. Many assessment methods used are portfolios, namely gathering work or documents that reflect the participants' abilities, knowledge, and achievements during the learning process. Formulation problem in study Why assessment portfolio Google form based must conducted on students class V SDN Tanjung Harapan, how implications or impact from implementation assessment portfolio based on Google form. Research purposes: To describe the implications or impact of the implementation assessment portfolio based on Google Forms. The research method used by the researcher is descriptive qualitative research. The descriptive method examines the status of a group of human, an object, a set of conditions, a system of thinking or a class of events in the present. Research results Based on Interviews with the science subject teacher, head school, and students Grade V SDN Tanjung Harapan results study This At the time carry out observation, shows that power educators, especially eye teachers lesson Knowledge Natural and Social Sciences (IPAS), experienced obstacle to participant students who have not to understand about How use of google form. Research conclusion An assessment portfolio is a procedure for collecting information regarding the development and capabilities of participant education through its portfolio, where information collection is done formally using specific criteria for objective decision-making regarding participant status.